1969
DOI: 10.1002/art.1780120608
|View full text |Cite
|
Sign up to set email alerts
|

Procainamide‐induced serologic changes in asymptomatic patients

Abstract: Serologic findings in cardiac patients who had no manifestations of drug-induced lupus and who had been taking procainamide for 6 weeks or more were compared to a similar group receiving quinidine, and a series of age-and sexmatched controls. Significant changes occurred only in the group of 22 patients ADD IN 1962 first described a case of L procainamide-induced systemic lupus erythematosus (SLE).l During the past 5 years an additional 49 cases have been reported.2-1S The entity has now become a well-recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1972
1972
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The production of various autoantibodies indicative of a state of autoimmunity has been observed commonly in patients treated with procainamide (PA)' for cardiac arrhythmia (1)(2)(3)(4)(5)(6). Prospective studies have revealed that PA may induce antinuclear antibodies in 50-83% of individuals, and that 12-29% of PA-treated patients develop a syndrome resembling systemic lupus erythematosus (SLE) (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of various autoantibodies indicative of a state of autoimmunity has been observed commonly in patients treated with procainamide (PA)' for cardiac arrhythmia (1)(2)(3)(4)(5)(6). Prospective studies have revealed that PA may induce antinuclear antibodies in 50-83% of individuals, and that 12-29% of PA-treated patients develop a syndrome resembling systemic lupus erythematosus (SLE) (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The development of autoimmunity induced by PA is influenced by factors that affect the serum level of this agent. These include dosage (2), duration of administration (8), and rate of acetylation of the parent drug (11). Thus, individuals who are slow acetylators maintain higher serum levels of PA and develop antinuclear antibodies sooner than those who are fast acetylators (11).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-dDNA is often found (3,22), but its relationship to the clinical manifestations have not been established. Data concerning the presence of anti-nDNA are conflicting (3,13,22,27).…”
mentioning
confidence: 99%
“…A Possible Explanation for Drug-induced Autoimmunity HARRY G. BLUESTEIN, DOUG REDELMAN, and NATHAN J. ZVAIFLER Procainamide therapy has been associated with a lupus erythematosus (LE) like illness. At least 50% of patients who take the drug for a long time develop antinuclear antibodies and approximately 10% of these develop the complete clinical syndrome (1)(2)(3). There has been considerable speculation about the pathogenesis of the drug-induced disease.…”
Section: Procainamide-lymphocyte Reactionsmentioning
confidence: 99%